Ce que savent les futurs enseignants de la Saskatchewan sur la phrase - Thibeault, Joël (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
Modern grammar, a paradigm that was incorporated into the Saskatchewan French curriculum in 2017, puts an important emphasis on syntax; in this perspective, it positions the sentence at the centre of the linguistic description it provides. This article, in order to see if future teachers in Saskatchewan are ready to teach grammar using this paradigm, describes what they know about sentences, and answers two questions. The first one focuses on our participants’ (N = 22) definition of the concept of sentence, while the second one aims to describe the ways through which they make judgements of grammaticality. Results show that a large portion of the criteria they use to define the concept of the sentence and judge the grammaticality of statements is syntactic, but that participants, who combine parts of speech and grammatical functions in their discourse do not show linguistic coherence. Through this study, we also identify a few grammatical components that should be explored in depth as future teachers are being trained. Keywords: sentence, future teachers, modern grammar, minority context, teacher training